Analisa Kinerja Dewan Pengawas Syariah di Bank Syariah - Rahma Yudi Astuti (University of Darussalam Gontor, 2015)
Sharia Supervisory Board (SSB) comprehensively supervise the overall product of Islamic banks. SSB then serves also as auditor of sharia is the answer to the emerging challenges of how to supervise Islamic economic institutions to remain current in accordance with the provisions of Islamic Sharia. Based on the above issues of interest to delakukan research on the role and responsibilities of the Sharia Supervisory Board of Islamic Banks. Through this study the authors wanted to know how an application in the field of surveillance conducted by SSB, by analyzing the regulations issued either BI or National Shariah Council. In its analysis the authors use an empirical approach and an analytical approach to analyze the problem was examined by field work with interviews and questionnaires for the next question was whether the line with the norms set by Bank Indonesia. The approach used is to better determine the extent to which the roles and responsibilities of SSB in the homeland. From the results obtained by analysis of the answers that the surveillance conducted by SSB against Islamic Bank has not fully maximized. In fact, only a small portion has actually supervise properly. Then the realization that SSB is the most important and influential in the Islamic Bank have not fully realized that in the end SSB participation in the daily activities of the bank can not do. Even the arrival of SSB against Islamic Bank to conduct surveillance is also very rare.